DEVELOPMENT OF A PROBLEM-SOLVING-BASED E-MAGAZINE ASSISTED BY A VIRTUAL LABORATORY ON TEMPERATURE AND HEAT MATERIALS FOR SEVENTH GRADE JUNIOR HIGH SCHOOL STUDENTS - Lestari, Auliasyura; Silitonga, Haratua Tiur Maria; Hidayatullah, Muhammad Musa Syarif (Universitas Tanjungpura, 2025)
This research aims to develop a problem-solving-based e-magazine learning media assisted by a virtual laboratory on temperature and heat material for grade VII junior high school students. The development of this e-magazine uses a research and development method with the ADDIE model. The subject of this research is students of class VII G SMP Negeri 6 Pontianak. Data collection techniques are carried out by means of observation, interviews, questionnaires, as well as pretest and posttest. The results of the study based on expert tests show the feasibility of e-magazines with an average score of 0.8 with very high validity criteria. The implementation in the learning process showed the acquisition of an effect size value of 1.97 with the category of large effectiveness and the results of the analysis of students' problem-solving skills at each step in the Heller problem-solving strategy showed an average N-gain value of 0.49 with the medium category. The results of the students' response in the field trial showed a percentage of 80.75% with a very high category. From the acquisition of these data, it can be concluded that e-magazines based on problem solving assisted by virtual laboratories on temperature and heat materials can help the learning process of students and help improve problem-solving skills on temperature and heat materials.